PERAN JARINGAN GUSDURIAN DALAM GERAKAN TOLERANSI BERAGAMA - Jonathan Tonggi Sitorus; Nely Larasati; Fira Sulistiani; Ilal ilham; Vieronica Varbi Sununianti (Bajang Institute, 2024)
The gusdurian network is an open movement, the gusdurian network was established in 2010 in Surabaya. This movement emerged with the aim of imitating the 9 values of Gus Dur, namely monotheism, humanity, justice, equality, liberation, brotherhood, simplicity, chivalry, and traditional wisdom. This article uses the relevance of Singh's identity theory to find out how these gusdurian networks are able to maintain their identity as a new social movement that aims to instill religious tolerance. The method used in this article is a literature review method by collecting 20 relevant articles on gusdurian tissue. The results of research from the review literature show that first, the Gusdurian network strives to continue to maintain their identity in the midst of the diversity of society as a religious movement that instills religious tolerance. second, the movement held by the Gusdurian network in an effort to instill the values of tolerance, namely the celebration of Tolerance Day, interfaith meetings, and creating content uploaded on @jaringan Gusdurian's Instagram account. In addition, the Gusdurian network strives to continue to maintain their identity in the midst of the diversity of society as a religious movement that instills religious tolerance. Thus, it can be concluded that the purpose of this paper is to introduce more widely to the public about the Gusdurian Network, to know how the Gusdurian Network can maintain their identity as an organization engaged in imitating religious tolerance, and to understand what strategies are applied by the Gusdurian Network to maintain the value of tolerance instilled by Gus Dur as the father of pluralism in Indonesia.